Hazard characterization for pathogens in food and water : guidelines (WHO, 2003)
Hazard characterization, either as part of a microbiological risk assessment or as a stand-alone process, describes the human adverse health effects that may result from ingestion of pathogenic microorganisms. Ideally, it will include quantitative information in terms of a dose-response relation and the probability of adverse outcomes. This volume provides guidelines for the characterization of hazards in food and water using a structured, six-step approach, involving a description of the process of hazard characterization, process initiation, data collection and evaluation, descriptive characterization, dose-response modeling, and review of results. This volume and others in the Microbiological Risk Assessment Series contain information that is useful to both risk assessors and risk managers, including international scientific committees, the Codex Alimentarius Commission, governments and food regulatory agencies, scientists, food producers and industries and other people or institutions with an interest in the area of microbiological hazards in foods, their impact on public health and food trade, and their control.
Microbiological risk assessment series, ISSN 1726-5274 no. 3
Keywords: zemědělství a potravinářství; směrnice jako téma; Food Microbiology; mikrobiologie, lékařská mikrobiologie; potravinářská mikrobiologie; Water Microbiology; hodnocení rizik; statistické modely; mikrobiologie vody; Models, Statistical; Guidelines as Topic; Risk Assessment; nutriční terapie, dietoterapie a výživa